Metodologia OKR aplicada em objetivos estratégicos voltados a ESG em uma empresa brasileira de cosméticos - Anguita, Camila do Nascimento (Universidade Federal de São Carlos, 2023)
The Objectives and Key Results (OKR) methodology seeks to define major objectives for the company and unfold them in the form of quantifiable key results with the creation of cross-functional teams to carry out activities and define their own key results. Another point that is increasingly debated by companies are goals related to environmental, social and corporate governance (ESG), and effective ways to achieve them, as the importance of this movement in the corporate culture and financial gains is already understood. In this sense, the present work aimed to analyze the implementation of the OKR methodology and its deployment for the ESG area, in a company in the cosmetics sector, through a qualitative research, based on the accomplishment of a case study , through interviews with employees of the organization. The results showed real gains in collaboration, transparency, engagement and a global performance in ESG at all levels of the company, with opportunities for improvement in order to get closer and closer to the theoretical model, such as decoupling goals from variable remuneration and adjustment of ESG goals to the short term. In this way, the implementation of the OKR methodology and its deployment in ESG brought advantages to the organization and influenced the employee's work model, strengthening relationships and the performance of the whole towards sustainable themes.
OKR methodology applied to strategic objectives focused on ESG in a Brazilian cosmetics company
Keywords: Objetivos e Resultados-chave; Metodologia OKR; ESG; Sustentabilidade; Cosméticos; Objectives and Key Results; Sustainability; OKR Methodology; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO